3D evaluation of the effects of traumatic surgical techniques on Vomer bone volume and morphology in the treatment of lip and palate clefts - ÇELEBİLER, ÖZHAN BEKİR; DURMUŞ KOCAASLAN, FATMA NİHAL (My University, 2022)
BACKGROUND: Cleft lip/palate (CLP) deformity is the most common congenital facial anomaly. In this study, it was aimed to evaluate the changes in volume and shape of Vomer bone after CLP repair surgery. METHODS: The images of a total of 30 patients aged between 9 and 12 years which were recorded with computed tomography were retrospectively analyzed. The patients were divided into three groups: No syndrome, operated for unilateral CLP group (n=10), no syndrome, operated for bilateral CLP group (n=10), and control group (n=10) with no syndrome, no operation history, or no lip/ palate deformities. Data of the patients were transferred to a software program and a new three-dimensional image was created for the Vomer. RESULTS: There was no statistically significant difference in the Sella-Nasion lengths, Vomer base lengths, and Vomer vertical lengths among the three groups. However, the Vomer bone volume of the patients with bilateral CLP was found to be statistically significantly higher than the control group. CONCLUSION: We can conclude that more bone formation may be observed due to the periosteal reaction following bilateral Vomer flap elevation or during maxillary growth, tension on the palatal flap may be increased new bone formation by pulling the bilateral Vomer flap if it is elevated and sutured palatal mucoperiosteal flap in the early period. Our findings have led us to the conclusion that size and volume of the Vomer bone can be significantly affected by environmental factors. According to the functional matrix theory, scar tissue formation and lack of Vomer-maxilla fusion cannot stimulate the further development of the anterior cranial bones, leading to shorter anterior cranial base.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Acil Tıp; Medicine; Health Sciences; Surgery Medicine Sciences; Emergency Medicine; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Emergency Medical Services; Cleft lip; palate; computed tomography; surgical trauma; veau-wardill-kilner palatoplasty; GROWTH; OCCLUSION; CHILDREN; REPAIR; HARD